Lidocaine loaded gelatin/gelatinized tapioca starch films for buccal delivery and the irritancy evaluation using chick chorioallantoic membrane - Suchipha Wannaphatchaiyong; Paul Wan Sia Heng; Jirapornchai Suksaeree; Prapaporn Boonme; Wiwat Pichayakorn (Elsevier, 2019)
The aim of this study was to confirm the feasibility of gelatin/gelatinized tapioca starch (α st) films for buccal delivery and to evaluate their irritancy. Lidocaine (LB) and lidocaine hydrochloride (LH) were used as model drugs and glycerin was used as the plasticizer. The scanning electron microscopy, atomic force electron microscopy, X-ray diffraction and thermogravimetric analysis results confirmed the compatibility of gelatin/α st/glycerin (Gαgly) films. Drug releases of LB- or LH-Gαgly films were evaluated. The drug release profiles of medicated films presented good patterns in both short time and 8 h drug release studies. The permeation study was examined through chick chorioallantoic membrane (CAM) by using modified Franz diffusion cells. Moreover, the irritancy study for buccal films was also examined by a hen's egg test on CAM model (HET-CAM). The results revealed that LB and LH could permeate through CAM, and these Gαgly films created no irritation on HET-CAM. This indicates that the LB- and LH-Gαgly films are possible to use as buccal films. Keywords: Gelatin, Gelatinized tapioca starch, Buccal film, Chick chorioallantoic membrane